Quantitative Hemodynamic Measurements in Cortical Vessels Using Functional Ultrasound Imaging - Brunner, Clément; Macé, Emilie; Montaldo, Gabriel; Urban, Alan (Frontiers in Neuroscience, 2022)
Red blood cells velocity (RBCv), cerebral blood flow (CBF), and volume (CBV) are three key parameters when describing brain hemodynamics. Functional ultrasound imaging is a Doppler-based method allowing for real-time measurement of relative CBV at high spatiotemporal resolution (100×110×300 µm3, up to 10 Hz) and large scale. Nevertheless, the measure of RBCv and CBF in small cortical vessels with functional ultrasound imaging remains challenging because of their orientation and size, which impairs the ability to perform precise measurements. We designed a directional flow filter to overpass these limitations allowing us to measure RBCv in single vessels using a standard functional ultrasound imaging system without contrast agents (e.g., microbubbles). This method allows to quickly extract the number of vessels in the cortex that was estimated to be approximately 650/cm3 in adult rats, with a 55-45% ratio for penetrating arterioles versus ascending venules. Then, we analyzed the changes in RBCv in these vessels during forepaw stimulation. We observed that ~40 vessels located in the primary somatosensory forelimb cortex display a significant increase of the RBCv (median ∆RBCv ~15%, maximal ∆ RBCv ~60%). As expected, we show that RBCv was higher for penetrating arterioles located in the center than in the periphery of the activated area. The proposed approach extends the capabilities of functional ultrasound imaging, which may contribute to a better understanding of the neurovascular coupling at the brain-wide scale.